Influence of “Nicoflok” Polymer-Mineral with Portland Cement on Granular Soils and Recycled Asphalt Material - Baroughi, Mahdi Zirak; Rezaei, Amir Hassan; Katebi, Hooshang (The Baltic Journal of Road and Bridge Engineering, 2020)
In road construction projects, due to the high volume of soil materials, the costs of supplying and transporting high-quality materials are very high, they may also include the crossing between different geotechnical lands with different types of soils and soil stabilization used to modify resistance characteristics of soil materials in different layers of the road. Addition of a stabilizing agent can improve the properties of aggregates and subgrade soils. In this study, the effect caused by the combined action of polymer-mineral composition “Nicoflok” and cement stabilization on the strength characteristics and durability of local materials, adopted from under-construction Ilkhchi highway project, was investigated. In addition, the effects of stabilizers on the recycled asphalt materials was studied to assess the possibility of using them in the pavement structure. Samples with 0, 0.5, 0.9 and 1.3 percent of Nicoflok combined with varying percentages of cement content were made and CBR tests were conducted after curing. Strength degradation of samples under 50 cycles of freeze-thaw was also investigated. The results show that addition of cement- Nicoflok admixture to the subgrade soil considerably increases CBR values, which leads to reduction of the required material amount. The efficiency of this polymer with Portland cement depends on several factors, such as the amount of cement, curing time, size and shape of soil grains. The optimum dosage of Nicoflok was 0.9% mixed with 1% cement. Stabilizing the base and recycled asphalt materials with cement and Nicoflok also improves the long-term performance of the pavement.